Comparative study of soil properties under Chromolaena odorata, Pueraria phaseoloides and Calliandra calothyrsus - Koutika, Lydie-Stella; Hauser, S.; Kamga, J.M.; Yerima, B. (Springer, 2005)
Fallows improve soil fertility and allow sustainable agriculture. Soil fertility was assessed under different types of fallow through pH, nutrient concentrations and particulate organic matter (POM) quantity and quality. The two year-fallows were under Chromolaena odorata, Calliandra calothyrsus and Pueraria phaseoloides on a Typic Kandiudult. Soils were sampled from 0–10 cm and 10–20 cm depth. The weight of POM was 2 mg g−1 of soil under Calliandra, 3.9 mg g−1 under Chromolaena and 3.7 mg g−1 under Pueraria in the 0–10 cm layer. The tPOM-C (proportion of C in the total POM) and tPOM-N (proportion of N in total POM) were 26.1% and 14.5% under Calliandra, 39.6% and 18.8% under Chromolaena and 37.0% and 16.7% under Pueraria. However, despite the improvement of soil fertility under Pueraria as compared to planted Calliandra, the effect of Pueraria on nutrient concentration and POM status remained similar to that of Chromolaena. Calliandra increased soil acidity and allowed a deterioration of nutrient concentration (Ca, K), ECEC and an impoverishment of POM status.